2013
DOI: 10.1161/circresaha.113.301783
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Propagation of Calcium Waves and Ultrastructural Remodeling in Recessive Catecholaminergic Polymorphic Ventricular Tachycardia

Abstract: C atecholaminergic polymorphic ventricular tachycardia (CPVT) is an inherited arrhythmogenic disease characterized by stress-and emotion-induced life-threatening arrhythmias. Mutations in the cardiac ryanodine receptor-2 (RyR2) and cardiac calsequestrin-2 (CASQ2) genes have been associated with the autosomal-dominant and the autosomalrecessive forms of CPVT.1 Knock-in mouse models that carry gain-of-function RyR2 mutations exhibit phenotypes similar to the clinical manifestations observed in patients with CPVT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
46
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 34 publications
5
46
1
Order By: Relevance
“…10,18,23 Furthermore, we observed an absence of the electron-dense CASQ2 polymer in the jSR cisternae.…”
Section: Architecture Of Crusmentioning
confidence: 62%
See 1 more Smart Citation
“…10,18,23 Furthermore, we observed an absence of the electron-dense CASQ2 polymer in the jSR cisternae.…”
Section: Architecture Of Crusmentioning
confidence: 62%
“…Interestingly, we have shown that our gene therapy strategy is able to recover protein levels and to revert the jSR widening and fragmentation 23 seen in CRUs of R33Q. 10 It is also remarkable that electron microscopy allowed to appreciate the correct localization of the overexpressed CASQ2 in the jSR as documented by the reappearance of the chain-like polymers of CASQ2 in the jSR.…”
Section: Discussionmentioning
confidence: 84%
“…However, SR Ca 2+ release can also occur spontaneously, as observed in a variety of pathological conditions ranging from heart failure (8,9) to ischemia (10) to catecholaminergic polymorphic ventricular tachycardia (11)(12)(13)(14). Spontaneous Ca 2+ release (SCR) transiently elevates the cytosolic Ca 2+ concentration ([Ca] i ), which in turn increases the forward mode of the electrogenic Na + /Ca 2+ exchange (NCX) current (I NCX ).…”
mentioning
confidence: 99%
“…Thanks to the presence of several mouse models of CPVT that recapitulate the clinical phenotype of the disease, the understanding of arrhythmogenic mechanisms has advanced rapidly. 117 We now know that mutations in the RYR2 and CASQ2 genes lead to spontaneous diastolic Ca 2+ release that by increasing Ca 2+ levels in the cytosol activates the Na + / Ca 2+ antiporter. In the attempt to normalize Ca 2+ levels, the Na + /Ca 2+ antiporter extrudes Ca…”
Section: Arrhythmogenic Mechanismsmentioning
confidence: 99%
“…117 Interestingly, the availability of animal models and of mechanistic understanding of the disease have allowed the advancement of therapeutic strategies. Watanabe et al 118 reported that flecainide is able to specifically attenuate calcium release by binding the RyR and by doing so can inhibit triggered activity.…”
Section: +mentioning
confidence: 99%